2011
DOI: 10.2217/pgs.10.196
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Comprehensive Panel of Biomarkers to Predict Response to a Fluorouracil–Oxaliplatin Regimen in Patients with Metastatic Colorectal Cancer

Abstract: In metastatic colorectal cancer patients treated with mFolfox-6, the combination of haplotype XPD Lys751Gln-GSTP1 105Val seems to predict the risk of progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 28 publications
3
27
0
1
Order By: Relevance
“…However, the opposite association was identified by two separate studies (Gan et al, 2012;Li et al, 2012), and three studies failed to provide evidence of any correlation (Martinez-Balibrea et al, 2008;Lamas et al, 2011;Kumamoto et al, 2013). Pooling the data in our analysis demonstrated that the XPD 751Gln allele showed a non-significant relationship with low objective response, and a marked association with short PFS and OS in patients overall, in Caucasians and especially in Asians in dominant model, which is consistent with the findings of the previous meta-analysis by Ming Yin et al (2011) However, subgroup analysis by ethnicity in homozygous comparison found that the Gln/ Gln genotype was significantly associated with favorable OS in Asians but with unfavorable OS in Caucasian.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, the opposite association was identified by two separate studies (Gan et al, 2012;Li et al, 2012), and three studies failed to provide evidence of any correlation (Martinez-Balibrea et al, 2008;Lamas et al, 2011;Kumamoto et al, 2013). Pooling the data in our analysis demonstrated that the XPD 751Gln allele showed a non-significant relationship with low objective response, and a marked association with short PFS and OS in patients overall, in Caucasians and especially in Asians in dominant model, which is consistent with the findings of the previous meta-analysis by Ming Yin et al (2011) However, subgroup analysis by ethnicity in homozygous comparison found that the Gln/ Gln genotype was significantly associated with favorable OS in Asians but with unfavorable OS in Caucasian.…”
Section: Discussionmentioning
confidence: 95%
“…By contrast, one article consisted of two independent studies, and studies included in this article were treated as separate studies (MartinezBalibrea et al, 2008). As a result, a total of 2286 CRC patients were enrolled in the 17 studies included in the pool analysis (Park et al, 2001;Stoehlmacher et al, 2004;Le Morvan et al, 2007;Ruzzo et al, 2007;Martinez-Balibrea et al, 2008;Pare et al, 2008;Lai et al, 2009;Boige et al, 2010;Chen et al, 2010;Etienne-Grimaldi et al, 2010;Farina Sarasqueta et al, 2011;Lamas et al, 2011;Chen et al, 2012;Gan et al, 2012;Li et al, 2012;Kumamoto et al, 2013). The selection procedure is shown in Figure 1, and the key patient characteristics are listed by study in Table 1.…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this predictive value of XRCC1 Arg399Gln (1 196G>A) was inconsistent with the results from a multiple genetic polymorphism study of biomarkers to predict response to a fluorouraciloxaliplatin regimen in patients with metastatic CRC (Lamas et al, 2011). It is a frequent phenomenon in biomarker research.…”
Section: Molecular Markers Of Oxaliplatinmentioning
confidence: 89%
“…Standard therapies for CRC include 5-fluorouracil and oxaliplatin (FOLFOX). One study looked at the role of germline variants of DNA repair pathways on metastatic CRC patients' response to FOLFOX (Lamas et al, 2011). One variant in XPD, Lys751Gln, was associated with longer survival, but the numbers in this study were small.…”
Section: Variants To Predict Response To and Off-target Effects Of Camentioning
confidence: 92%